Match duration and number of rallies in men´s and women´s 2000-2010 FIVB world tour beach volleyball - Palao, J. M.; Valades, D.; Ortega, E. (Journal of Human Kinetics, 2012)
After the 2000 Olympic Games, the Fédération Internationale de Volleyball (FIVB) modified the scoring system used in beach volleyball from side-out to a rally point system. The goal was to facilitate the comprehension of the game and to stabilize match duration. The purpose of this study was to assess the duration and number of rallies in men´s and women´s beach volleyball matches (2000-2010 FIVB World Tour). Data from 14,432 men´s matches and 14,175 women´s matches of the 2000-2010 World Tour were collected. The variables studied were: match duration, total rallies per set and match, number of sets, team that won the set and match, type of match (equality in score), and gender. The average match duration in beach volleyball is stable, ranging from 30 to 64 minutes, regardless of the number of sets, the stage of the tournament (qualifying round or main draw), or gender. The average number of rallies per match were 78-80 for two-set matches and 94-96 for three-set matches. Matches from the main draw are more balanced than matches from the qualifying round. More balanced matches (smaller point difference between teams) have longer durations. It is not clear why there is no relationship between the number of rallies and match duration. Future studies are needed to clarify this aspect. The results can serve as a reference to guide beach volleyball training (with regard to duration and number of rallies) and to help understand the effect of the rule change